Therapy for psoriatic arthritis with infliximab - V V Badokin; Yu L Korsakova; V G Barskova; M S Eliseyev; F M Kudayeva (Современная ревматология)
Objective: to study the efficacy and tolerability of infliximab (Remicade) in the major syndromes of psoriatic arthritis (PA). Subjects and methods. The study was based on Remicade therapy in 22 patients with severe and moderate PA with polyarthritic, osteolytic and spondyloarthritic types of the joint syndrome, generalized psoriasis vulgar and erythrodermata, and pustular psoriasis. Inflammatory activity was determined by DAS 4 and the efficiency of therapy was evaluated by the ACR and EULAR criteria. The severity of psoriasis was judged from the PASI index. Inefficiency or intolerability of essential anti-inflammatory drugs (EAIDs) was observed in all the patients. Therapy with Remicade in combination with methotrexate was performed in 7 patients; the other patients took Remicade without EAIDs. The drug was intravenously injected in a dose of 5 mg/kg by the generally accepted scheme. The efficacy of the first 5 Remicade infusions was evaluated. Results. Just after the first infliximab infusion, there was a significant reduction in the intensity of joint pains and in the duration of morning stiffness, as well as in the number of tender and inflamed joints. The improvement was associated with the duration of treatment. Remicade therapy resulted in diminished inflammatory activity. Before treatment the high activity of PA, estimated from the DAS 4 index, was determined in 71,4% of the patients; and after the second infusion it was seen only in 5%. After three infusions or more, there were a larger number of patients with 70ACR scores, i.e. those with a very good effect of therapy; and after 5 infusions; the number of such patients was as high as 91%. According with the EULAR criteria, a good therapeutic effect was observed in 89% of cases. The course of psoriasis was less pronounced. PA remission occurred in every 6 and every 3 patients after the second and fifth infusions, respectively. Conclusion. Remicade is the most effective drug among the available anti-inflammatory ones for the treatment of PA. It strongly affects the major syndromes of this disease.